The Pricing of Vulnerable Options in a Fractional Brownian Motion Environment - Chao Wang; Shengwu Zhou; Jingyuan Yang (Discrete Dynamics in Nature and Society)
Under the assumption of the stock price, interest rate, and default intensity obeying the stochastic differential equation driven by fractional Brownian motion, the jump-diffusion model is established for the financial market in fractional Brownian motion setting. With the changes of measures, the traditional pricing method is simplified and the general pricing formula is obtained for the European vulnerable option with stochastic interest rate. At the same time, the explicit expression for it comes into being.